Telecollaboration in Spanish as a Foreign Language in Trinidad - Neva, Carolina; Landa, María; Carter, Beverly Anne; Ibrahim-Ali, Amina (Íkala, Revista de Lenguaje y Cultura, 2010)
The objective is to study how participation in tandem partnership influences the motivation towards the target language and culture and the autonomy of learners of Spanish as a foreign language in Trinidad and Tobago. For this reason, an action research project was conducted with thirty-three learners of Spanish in Trinidad and thirty-three learners of English in Colombia, who engaged in a seven week tele-collaboration during which they used email and Web 2.0 technologies to communicate. Data were collected through questionnaires and a weekly journal. Quantitative and qualitative analyses were carried out. As a result the project was a rich source of learning for all the participants and stresses the need of a deeper understanding of learners' language learning, an analysis of the sociocultural, psycholinguistic, and linguistic dimensions of intercultural competence in a specific context, and the critical assessment of the role of Web 2.0 technologies in fostering autonomy. Received: 26-08-09 /Accepted: 28-02-10 How to reference this article: Neva, C.; Landa-Buil, M.; Carter, B.-A. & Ibrahim-Ali, A. Telecollaboration in Spanish as a Foreign Language in Trinidad. Íkala [online]. 2010, vol.15, n.24, pp.75-102.